2019
DOI: 10.1007/s00535-019-01642-1
|View full text |Cite
|
Sign up to set email alerts
|

REFLECT—a phase 3 trial comparing efficacy and safety of lenvatinib to sorafenib for the treatment of unresectable hepatocellular carcinoma: an analysis of Japanese subset

Abstract: Background A phase 3, multinational, randomized, noninferiority trial (REFLECT) compared the efficacy and safety of lenvatinib (LEN) and sorafenib (SOR) in patients with unresectable hepatocellular carcinoma (uHCC). LEN had an effect on overall survival (OS) compared to SOR, statistically confirmed by non-inferiority [OS: median = 13.6 months vs. 12.3 months; hazard ratio (HR) 0.92, 95% confidence interval (CI) 0.79-1.06], and demonstrated statistically significant improvements in progression-free survival (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
143
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(170 citation statements)
references
References 39 publications
(71 reference statements)
21
143
4
2
Order By: Relevance
“…Additionally, when we used the standard cut-off value for objective response, that is, ETS ≥ 30%, the specificity for predicting PFS was considerably worse, compared with ETS ≥ 10%, because only 15% of the patients achieved that ETS. In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, when we used the standard cut-off value for objective response, that is, ETS ≥ 30%, the specificity for predicting PFS was considerably worse, compared with ETS ≥ 10%, because only 15% of the patients achieved that ETS. In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in our study, the ORR and DCR were 33% and 74%, respectively. Yamashita et al previously reported an MST of 17.6 months in Japanese patients with unresectable HCC treated with LEN in a phase 3, multinational, randomized, non-inferiority trial (REFLECT) [33]. Thus, the therapeutic effect of LEN in our study appears to be similar to that reported previously [7,11,33], suggesting that the enrolled subjects and treatment effects in our study are typical.…”
Section: Discussionsupporting
confidence: 87%
“…however, the data were consistent with the results of a Japanese subpopulation analysis (ORR=61.3%) [16] Japanese subpopulation analysis [16]. Preserved liver function is an important factor for ORR and outcome of HCC patients in systemic therapy [36,37].…”
Section: Efficacy and Safetysupporting
confidence: 88%
“…In patients with intermediate-stage HCC, who had prior TACE history and become TACE failure, lenvatinib showed significantly and clinically meaningful anti-cancer efficacy by reducing tumour size or enhancement on dynamic CT in a large proportion of patients (ORR=61.3%) [9,[16][17][18]. In addition, systemic therapy has an advantage over TACE by preserving liver function during the treatment [19][20][21].…”
Section: Introductionmentioning
confidence: 99%